Effect of Polymer Concentration on Micromeritics, Kinetics, and Activity of Ciprofloxacin HCl-Alginate Microspheres - Hariyadi, Dewi Melani (Asian Journal of Pharmaceutics (AJP), 2019)
Purpose: This research was to design a sustain release system for ciprofloxacin HCl for inhalation delivery. Ciprofloxacin HCl was encapsulated with alginate polymer by aerosolization ionotropic gelation. Materials and Methods: Ciprofloxacin HCl-alginate microspheres formula consisted of 0.5–1.35% alginate polymer. Micromeritic properties, in vitro release, and kinetics of the formulations were characterized. Micromeritics properties were studied in terms of bulk and tapped density, Carr index, and Hausner ratio. In vitro drug release was studied in phosphate-buffered saline media pH 7.2 for 12 h. This research also studied the activity of ciprofloxacin HCl-alginate microspheres. Antibacterial activity test was carried out using in vitro diffusion technique using Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853 bacteria. Results: Release mechanism followed Higuchi model kinetics. The obtained freeze-dried microspheres showed good flow properties. From all formulas against S. aureus ATCC 25923, it was indicated that activity of all formula microspheres had higher activity compared to ciprofloxacin HCl and more stable. However, for formula against P. aeruginosa ATCC 27853, results showed that ciprofloxacin HCl was only effective at above 0.75% of alginate polymer. Furthermore, the encapsulation process and pH exposure did not affect in activity of ciprofloxacin HCl. Conclusion: These concluded that ciprofloxacin HCl-alginate microspheres were stable and potential for antibacterial activity.